Spiritual and Mental Guidance in Obedience to Prayer for Police Members in the Environment of Battalion A Pelopor Sat Brimob Polda Papua - Supirman Supirman; Neti S; Hasrudin Dute; Nurul Muthmainnah (Jurnal Riset Rumpun Agama dan Filsafat, 2024)
This study aims to: (1) identify and explain the picture of the obedience of prayer worship among Polri members in the environment of Battalion A Pelopor Sat Brimob Polda Papua; and (2) identify and explain the implementation of spiritual and mental guidance in improving the obedience of prayer worship among Polri members in the environment of Battalion A Pelopor Sat Brimob Polda Papua. This study uses a qualitative descriptive approach. The data sources in this study consist of primary data obtained from the leaders and members of Battalion A Pelopor Sat Brimob Polda Papua, as well as secondary data obtained from documents, books, and journals relevant to the study. The results of the study indicate that: (1) the obedience of prayer worship among Polri members in the environment of Battalion A Pelopor Sat Brimob Polda Papua has been implemented well, which is shown through the participation of members in worship activities at the Al-Muhajirin Brimob Kotaraja Mosque. This obedience is influenced by several supporting factors, including member discipline, support from the work environment and leaders, solidarity between members, and the availability of adequate worship facilities; (2) Spiritual and mental guidance (Binrohtal) is an official program implemented based on the Regulation of the Republic of Indonesia National Police Number 10 of 2018. This activity is held every Thursday after the morning roll call at the Al-Muhajirin Brimob Kotaraja Mosque and is attended by Muslim members. The activity includes reading Ummul Qur'an, Surah Yasin, reciting the Prophet's prayers, and delivering sermons by ustadz. Overall, spiritual and mental guidance activities play an important role in increasing obedience to worship, especially prayer, strengthening spiritual religious relationships, and helping Brimob members face challenges and pressures in carrying out their duties.